The importance of iron intake for children’s growth and development - Rini Sekartini (Indonesian Nutrition Association, 2020)
The impact of iron deficiency to children’s growth and development already starts since non-anemic iron deficiency phase. Impact of iron deficiency to school-aged children including decreased cognitive function, behavior problems, increased risk of infections, and stunting.